2024
DOI: 10.1002/jrs.6658
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced transformations in (As1–xBix)2S3 glass observed by Raman spectroscopy

Yuriy Azhniuk,
Vasyl Lopushansky,
Stepan Hasynets
et al.

Abstract: Raman spectra of (As1–xBix)2S3 glass samples with x ≤ 0.2 measured at the excitation with above‐bandgap (532 nm) laser light at a relatively low power density (Pexc = 4 kW/cm2) clearly confirm the amorphous character, thereby markedly extending the known compositional interval of existence of the (As1–xBix)2S3 glass previously known (x ≤ 0.06). Spectra measured at an increased Pexc (40 kW/cm2) reveal a photostructural transformation in the illuminated area of the glass leading to an additional contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Formation of arsenates can be strongly assisted by the presence of dopants in the arsenic chalcogenide, for instance, Pb [52]. Our recent Raman study of (As 1-x Bi x ) 2 S 3 glasses [53] confirmed that AsO 4 3ions are formed under visible-light illumination only at a noticeable amount of bismuth (x 0.14) while for the glasses with lower Bi content no signs of oxidation were observed. On the other hand, it is known that doping amorphous As 2 Se 3 with metals prevents (in case of Cu dopant) or inhibits (doping with Ag) the photooxidation reactions on the surface [21].…”
Section: Discussionmentioning
confidence: 66%
“…Formation of arsenates can be strongly assisted by the presence of dopants in the arsenic chalcogenide, for instance, Pb [52]. Our recent Raman study of (As 1-x Bi x ) 2 S 3 glasses [53] confirmed that AsO 4 3ions are formed under visible-light illumination only at a noticeable amount of bismuth (x 0.14) while for the glasses with lower Bi content no signs of oxidation were observed. On the other hand, it is known that doping amorphous As 2 Se 3 with metals prevents (in case of Cu dopant) or inhibits (doping with Ag) the photooxidation reactions on the surface [21].…”
Section: Discussionmentioning
confidence: 66%